Concrete suitable for chloride salt dry and wet environment and preparation method thereof
By using optimized proportions of nanomaterials and basalt fibers and compounded mineral blends in concrete, the microstructure of concrete is improved, the problem of degradation of concrete performance in chloride-salt-dry wet environment is solved, and high strength and good Durability and anti-chlorine ion corrosion properties.
Patent Information
- Application Number
- CN202310795622.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-30
AI Technical Summary
In a wet and dry environment of chloride, the mechanical properties and durability of concrete drop sharply, resulting in structural corrosion and damage, affecting the safety of buildings and structures.
Using optimized ratio nanomaterials and basalt fibers and compounded mineral blends, the density and chemical curing ability of the gelled materials are improved by improving the microstructure and particle grading of concrete, and the density and chemical curing ability of the gelled materials are improved, and suitable for the wet and dry environment of chloride salt are prepared. concrete.
It significantly improves the compressive strength, split tensile strength and durability of concrete, reduces the depth of chloride ion erosion, extends the service life, and improves the resistance to chloride salt corrosion.
Smart Images

Figure BDA0004314928170000061 
Figure BDA0004314928170000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to concrete suitable for chloride salt dry and wet environments and a preparation method thereof. Background Art
[0002] Concrete is a material widely used in engineering fields such as construction, roads, and bridges. However, in chloride-rich environments such as coastal areas and salt lake areas, concrete is subjected to long-term dry and wet erosion by chloride salts, which leads to a sharp decline in the mechanical properties and durability of concrete, and a significant reduction in its service life. Concrete structures often suffer from corrosion damage due to insufficient durability before reaching their designed service life, seriously affecting the safety of buildings and structures. Therefore, it is very necessary to study how to improve the mechanical properties and chloride ion corrosion resistance of concrete under dry-wet cycle conditions.
[0003] Adding mineral admixtures and fibers is an effective way to improve the overall performance of concrete. Replacing cement with mineral admixtures such as fly ash, silica fume, and slag powder is the most practical and economical way to reduce carbon emissions and promote sustainable green development of concrete buildings. Compared with single-mixed mineral admixtures, concrete with composite mineral admixtures and fibers has better resistance to chloride ion erosion. This is because after adding multiple mineral admixtures, multiple composite effects such as volcanic ash effect and micro-aggregate effect will occur inside the concrete. The particle gradation of composite mineral admixtures is more uniform, and cementitious materials of different particle sizes fill each other, so that the cementitious material powder is closely stacked and has good continuous gradation. In addition, fibers can significantly improve the interface structure and pore structure of concrete, effectively alleviating the damage caused by chloride salt erosion to concrete.
[0004] As a rapidly developing emerging material, nanomaterials have fine particles, large specific surface area, strong surface adsorption capacity, good filling effect and active effect, which make them have unique advantages in promoting cement hydration. Nano-SiO2 and nano-CaCO3 have the advantages of high mechanical strength and environmental protection. Adding nano-SiO2 to concrete reduces the penetration of corrosive media - chloride ions. Its secondary hydration and dispersed filling densification effect make the pore structure of concrete highly refined, the microstructure more dense, and improve the concrete's resistance to chloride ion penetration. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a concrete suitable for chloride salt dry and wet environments.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: by weight, comprising:
[0009] 1087-1106 parts of coarse aggregate, 623-643 parts of fine aggregate, 267-298 parts of cement, 57-74 parts of fly ash, 39-48 parts of silica fume, 44-53 parts of slag powder, 2.21-8.82 parts of nano-SiO2, 3.53-7.94 parts of nano-CaCO3, 3.09-7.50 parts of basalt fiber, 0.04-0.13 parts of defoaming agent, 2.21-3.09 parts of water reducing agent, and 158-167 parts of water.
[0010] As a preferred solution of the concrete suitable for chloride salt dry and wet environment described in the present invention, the mass ratio of cement, fly ash, silica fume and slag powder is 13:3:2:2, the basalt fiber content is 1.2%, the nano-SiO2 content is 1%, and the nano-CaCO3 content is 1.3%.
[0011] The preferred composite mineral admixtures of the present invention - cement, fly ash, silica fume, and slag powder - significantly improve the workability of the concrete mixing state. At the same time, the characteristics of the mineral components, chemical composition, and particle morphology of the cementitious materials effectively fill the micropores inside the concrete, achieve close stacking, and make the microstructure more compact. Among them, fly ash and slag powder can provide more C3A and Ca(OH)2 to react with chloride ions to generate Friedel's with smaller interlayer spacing, thereby chemically solidifying the chloride ions; silica fume promotes the formation of CSH gel, thereby physically adsorbing the chloride ions. The composite reinforcement effect of mineral admixtures can effectively inhibit the deterioration of chloride salt erosion.
[0012] As a preferred embodiment of the concrete suitable for chloride salt dry and wet environment described in the present invention, after 60 dry-wet cycles, the concrete has a compressive strength of ≥47MPa, a splitting tensile strength of ≥4.8MPa, a mass loss rate of ≤1.2%, a relative dynamic elastic modulus of ≥90%, and a chloride ion erosion depth of ≤16mm.
[0013] As a preferred solution of the concrete suitable for chloride salt dry and wet environment described in the present invention, the coarse aggregate is granite crushed stone with a particle size of 5 to 25 mm, and the fine aggregate is river sand with a fineness modulus ≥2.4, a mud content ≤0.5%, and a particle size ≤4.75 mm.
[0014] As a preferred solution of the concrete suitable for chloride salt dry and wet environment described in the present invention, the cement is silicate cement with strength grade P.O52.5, the fly ash is Class I fly ash, with fineness ≤12%, water requirement ratio ≤95%, SiO2 content in the silica ash ≥97.8%, and specific surface area ≥20m 2 / g, loss on ignition ≤1.48%, chloride ion content ≤0.01wt%, and the slag powder is S105 grade slag powder with a loss on ignition ≤1.0%.
[0015] As a preferred solution of the concrete suitable for chloride salt dry and wet environment described in the present invention, the nano-SiO2 is a white spherical powder with a SiO2 content of ≥99.5% and a specific surface area of ≥240m 2 / g, an average particle size of 20±5nm, a sintering vector (950℃×2h)≤5, and the nano-CaCO3 is a white powder with an average particle size of 40nm.
[0016] As a preferred solution of the concrete suitable for chloride salt dry and wet environment of the present invention, the basalt fiber has a length of 6 mm, a diameter of 13-20 μm, and a density of 2.65 g / cm 3 .
[0017] As a preferred solution of the concrete suitable for chloride salt dry and wet environment described in the present invention, the pH of the defoamer is 6-8, the water reducing agent is a polycarboxylic acid high-performance water reducing agent, and the water reducing efficiency is 35%.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing concrete suitable for use in chloride salt dry and wet environments.
[0019] In order to solve the above technical problems, the present invention provides the following technical solution: the inner wall and blades of the mixer are wetted, coarse aggregate and fine aggregate are added into the mixer, and stirred at a speed of 80 to 120 r / min for 25 to 35 seconds;
[0020] After cement, fly ash, silica fume, slag powder and basalt fiber are evenly mixed, add them into a mixer and stir for 25 to 35 seconds, then continue to add water and stir for 25 to 35 seconds;
[0021] Nano-SiO2, nano-CaCO3, water reducing agent, defoaming agent and remaining water are mixed to prepare a suspension, and then the suspension is vibrated in an ultrasonic oscillator, and then added into a mixer and stirred for 60 seconds to obtain a concrete mixture;
[0022] The mixture is loaded into the mold, vibrated on a vibration table for 5 to 10 seconds, and after plastering, it is left to stand indoors for 24 hours before demoulding. It is then moved into a standard curing room and cured for 28 days to obtain concrete suitable for chloride salt dry and wet environments.
[0023] As a preferred embodiment of the method for preparing concrete suitable for chloride salt dry and wet environments of the present invention, the ratio of the weight of water to the total weight of the cement, fly ash, silica fume and slag powder during the continuous adding of water and stirring is 0.33 to 0.38.
[0024] Beneficial effects of the present invention:
[0025] The invention provides a formula of concrete suitable for a chloride salt dry and wet environment. By doping nano materials and basalt with optimized proportions into concrete, the mechanical properties, service life and chloride salt corrosion resistance of the concrete are improved. The prepared concrete has excellent performance. After 60 dry-wet cycles (120 days), the compressive strength is ≥47MPa, the splitting tensile strength is ≥4.8MPa, and the mechanical properties are good. The mass loss rate is ≤1.2%, the relative dynamic elastic modulus is ≥90%, and the durability is good. The chloride ion corrosion depth of the concrete is ≤16mm, and the chloride salt corrosion resistance is good. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] The concrete prepared by the present invention is subjected to a chloride salt dry and wet environment simulation test according to the following method:
[0030] During the wet-dry cycle test, the concentration of NaCl solution was 10% (mass fraction). The concrete specimen was immersed in the chloride solution for 22 hours, the surface moisture was wiped off, air-dried at room temperature for 2 hours, and then placed in a 60°C oven for drying for 22 hours, the surface moisture was wiped off, and air-dried at room temperature for 2 hours. This was one wet-dry cycle, and a total of 60 wet-dry cycles were performed in the entire test. To ensure that chloride ions were transmitted in one dimension, the remaining five surfaces of the concrete specimen were sealed with epoxy resin except for one side.
[0031] According to GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the compressive strength and splitting tensile strength were measured respectively;
[0032] According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the mass loss rate, relative dynamic elastic modulus and chloride ion corrosion depth were measured respectively.
[0033] The coarse aggregate used in the present invention is granite crushed stone with a particle size of 5 to 25 mm; the fine aggregate is river sand with a fineness modulus of ≥2.4, a mud content of ≤0.5%, and a particle size of ≤4.75 mm; the cement is ordinary Portland cement with a strength grade of P.O52.5; the fly ash is Class I fly ash with a fineness of ≤12% and a water requirement ratio of ≤95%; the SiO2 content in the silica ash is ≥97.8% and the specific surface area is ≥20m 2 / g, loss on ignition ≤1.48%, chloride ion content ≤0.01wt%; slag powder is S105 grade slag powder, loss on ignition ≤1.0%; nano-SiO2 is white spherical powder, SiO2 content ≥99.5%, specific surface area ≥240m 2 / g, average particle size is 20±5nm, sintering vector (950℃×2h)≤5; nano-CaCO3 is white powder, average particle size is 40nm; basalt fiber is 6mm long, 13~20μm in diameter, density is 2.65g / cm 3 ; The water reducing agent is a polycarboxylic acid high-performance water reducing agent with a water reducing efficiency of 35%.
[0034] The other raw materials used in the present invention are all commonly available in the market unless otherwise specified.
[0035] Example 1
[0036] This embodiment provides a method for preparing concrete suitable for chloride salt dry and wet environments, specifically:
[0037] 1) Weigh the following raw materials by weight:
[0038] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 4.41 parts of nano-SiO2, 5.73 parts of nano-CaCO3, 5.29 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, 163 parts of water;
[0039] 2) Preparation of concrete:
[0040] Take 25 parts of water to wet the inner wall of the mixer and its blades, add coarse aggregate and fine aggregate into the mixer and stir for 30 seconds;
[0041] After cement, fly ash, silica fume, slag powder and basalt fiber are mixed evenly, they are added into a mixer and stirred for 30 seconds, and then 69 parts of water are added into the mixer and stirred for 30 seconds;
[0042] Nano-SiO2, nano-CaCO3, water reducing agent, defoaming agent and remaining water are mixed to form a suspension, and then the suspension is vibrated in an ultrasonic oscillator, and then the suspension is added into a mixer and stirred for 60 seconds to obtain a concrete mixture;
[0043] The mixture is loaded into a mold, vibrated and compacted on a vibration table for 10 seconds, and after being plastered, it is left to stand indoors for 24 hours before demoulding. It is then moved into a standard curing room (temperature 20±2°C, relative humidity 95±3%) and cured for 28 days to obtain a concrete suitable for chloride salt dry and wet environments.
[0044] Example 2
[0045] The difference between this embodiment and embodiment 1 is that the formula of concrete is adjusted, and the specific formula is:
[0046] 1098 parts of coarse aggregate, 631 parts of fine aggregate, 297 parts of cement, 57 parts of fly ash, 40 parts of silica fume, 45 parts of slag powder, 2.21 parts of nano-SiO2, 3.53 parts of nano-CaCO3, 3.09 parts of basalt fiber, 0.04 parts of defoamer, 2.22 parts of water reducer, 161 parts of water;
[0047] The remaining preparation processes are the same as those in Example 1 to obtain the concrete of this example.
[0048] Example 3
[0049] The difference between this embodiment and embodiment 1 is that the formula of concrete is adjusted, and the specific formula is:
[0050] 1092 parts of aggregate, 638 parts of fine aggregate, 269 parts of cement, 74 parts of fly ash, 47 parts of silica fume, 52 parts of slag powder, 6.62 parts of nano-SiO2, 7.94 parts of nano-CaCO3, 7.50 parts of basalt fiber, 0.13 parts of defoamer, 3.09 parts of water reducer, 164 parts of water;
[0051] The rest of the preparation process is the same as that in Example 1 to obtain the concrete of this example.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 1 is that nano-CaCO3, nano-SiO2 and basalt fiber are not added to the concrete formula, and the specific formula is:
[0054] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water; the rest of the preparation process is the same as that of Comparative Example 1 to obtain the concrete of this comparative example.
[0055] The mechanical properties and chloride ion corrosion resistance depth of the concrete obtained in Examples 1 to 3 and Comparative Example 1 were measured, and the results are shown in Table 1.
[0056] Table 1 Concrete properties with different mix ratios
[0057]
[0058] It can be seen from the data in Table 1 that the concrete obtained by adding nanomaterials and compounding basalt in the present invention has excellent mechanical properties, and its resistance to chloride erosion is the best and the service life is the longest. In particular, in Example 1 of the present invention, when the ratio of cement, fly ash, silica fume and slag powder is 13:3:2:2, and the basalt fiber content is 1.2%, and the nano-SiO2 and nano-CaCO3 content is 1% and 1.3%, the performance improvement is most significant. This is because the particle gradation of the concrete is improved under this ratio, so that the pore filling therein is complementary, forming a composite complementary effect, thereby synergistically improving the physical adsorption and chemical curing ability of the concrete for chloride ions, and enhancing the matrix bonding strength and the resistance to chloride ion penetration.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 1 is that nano-CaCO3 and basalt fiber are not added to the concrete formula, and the specific formula is:
[0061] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 4.41 parts of nano-SiO2, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water; the rest of the preparation process is the same as that of Comparative Example 1 to obtain the concrete of this comparative example.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 1 is that nano-SiO2 and basalt fiber are not added to the concrete formula, and the specific formula is:
[0064] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 5.73 parts of nano-CaCO3, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water; the rest of the preparation process is the same as that of Comparative Example 1 to obtain the concrete of this comparative example.
[0065] Comparative Example 4
[0066] The difference between this comparative example and Example 1 is that nano-CaCO3 and nano-SiO2 are not added to the concrete formula, and the specific formula is:
[0067] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 5.29 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water; the rest of the preparation process is the same as that of Comparative Example 1, and the concrete of this comparative example is obtained.
[0068] Comparative Example 5
[0069] The difference between this comparative example and Example 1 is that the amount of nano-SiO2 added in the concrete formula is adjusted to 13.94 parts, and the specific formula is:
[0070] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 13.94 parts of nano-SiO2, 5.73 parts of nano-CaCO3, 5.29 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, 163 parts of water;
[0071] The remaining preparation processes are the same as those in Comparative Example 1 to obtain the concrete of this comparative example.
[0072] Comparative Example 6
[0073] The difference between this comparative example and Example 1 is that the amount of nano-CaCO3 added in the concrete formula is adjusted to 14.55 parts, and the specific formula is:
[0074] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 4.41 parts of nano-SiO2, 14.55 parts of nano-CaCO3, 5.29 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, 163 parts of water;
[0075] The remaining preparation processes are the same as those in Comparative Example 1 to obtain the concrete of this comparative example.
[0076] Comparative Example 7
[0077] The difference between this comparative example and Example 1 is that the amount of basalt fiber added in the concrete formula is adjusted to 15.44 parts, and the specific formula is:
[0078] 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 4.41 parts of nano-SiO2, 5.73 parts of nano-CaCO3, 15.44 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water; the rest of the preparation process is the same as that of Comparative Example 1 to obtain the concrete of this comparative example.
[0079] The mechanical properties and chloride ion corrosion resistance depth of the concrete obtained in Comparative Examples 2 to 7 were measured and compared with Example 1. The results are shown in Table 2.
[0080] Table 2 Properties of concrete obtained from different formulations
[0081]
[0082] Table 2 shows the performance of concrete obtained under different formulas and different proportions of admixtures, compared with the performance of concrete in Example 1. It can be seen from Comparative Examples 2 to 4 that only when nano-CaCO3, nano-SiO2 and basalt fiber are compounded can the overall improvement of the comprehensive performance of concrete be achieved.
[0083] Nano-SiO2 can fill the pores and cracks in concrete, increasing the density and strength of concrete, while nano-CaCO3 can promote the hydration reaction of concrete to form dense hydration products. When the two coexist, their interaction further improves the mechanical properties and durability of concrete. Basalt fiber added to concrete can prevent the expansion of cracks and increase the crack resistance of concrete, but its dispersion is poor and the interface bonding strength with the matrix is low. Nano-SiO2 can fill the pores between fibers and improve the bonding strength between fibers and the matrix. Nano-CaCO3 can improve the dispersion and distribution uniformity of basalt fibers in concrete, and combine with basalt fibers through physical or chemical bonds to enhance the mechanical connection between fibers and the matrix and improve the strength and toughness of concrete.
[0084] From the data of Comparative Examples 5 to 6, it can be seen that the ratio of the three when compounded also has a significant impact on the technical effect. Due to the synergistic effect among the three, if the amount of one of the raw materials is simply increased, it will not only fail to improve the performance of the concrete, but will further reduce the performance of the concrete. For example, the content of nano-CaCO3 in the solution of Comparative Example 6 is too high, and its comprehensive performance is reduced to a certain extent compared with Comparative Example 2 where no nano-CaCO3 is added. This is because simply adding nano-calcium carbonate will increase the viscosity of the concrete, making it difficult to effectively fill the gaps in the concrete, and it will form a certain pore structure itself, making the concrete susceptible to moisture and gas invasion, reducing the service life while reducing the density and strength of the concrete.
[0085] For another example, the basalt fiber content in the solution of Comparative Example 7 is too high. Compared with Comparative Examples 2 and 3 in which no basalt fiber is added, its mechanical properties, service life and chloride ion resistance effect are all reduced to a certain extent. As shown above, this is because the addition of basalt fiber in concrete has the problems of poor dispersibility and low bonding strength with the matrix. When its content is too high and the addition amount of nano-SiO2 and nano-CaCO3 is insufficient, it cannot be improved, resulting in the effect of excessive addition of basalt fiber being worse than that of no addition.
[0086] In summary, the present invention provides a concrete suitable for a chloride salt dry and wet environment and a preparation method thereof. By compounding nano-CaCO3, nano-SiO2 and basalt fiber and optimizing the proportion, and doping them into concrete, the prepared concrete has excellent performance. After 60 dry-wet cycles (120 days), the compressive strength is ≥47MPa, the splitting tensile strength is ≥4.8MPa, and the mechanical properties are good; the mass loss rate is ≤1.2%, the relative dynamic elastic modulus is ≥90%, and the durability is good; the chloride ion corrosion depth of the concrete is ≤16mm, the chloride salt corrosion resistance is good, the concrete has good economic and environmental benefits, and is suitable for popularization and use.
[0087] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A concrete suitable for chloride salt dry and wet environment, characterized by: In parts by weight, including: 1095 parts of coarse aggregate, 634 parts of fine aggregate, 284 parts of cement, 65 parts of fly ash, 44 parts of silica fume, 48 parts of slag powder, 4.41 parts of nano-SiO2, 5.73 parts of nano-CaCO3, 5.29 parts of basalt fiber, 0.09 parts of defoamer, 2.65 parts of water reducer, and 163 parts of water.
2. The concrete suitable for chloride salt dry and wet environment as claimed in claim 1, characterized in that: After 60 dry-wet cycles, the concrete has a compressive strength of ≥47 MPa, a splitting tensile strength of ≥4.8 MPa, a mass loss rate of ≤1.2%, a relative dynamic elastic modulus of ≥90%, and a chloride ion corrosion depth of ≤16 mm.
3. The concrete suitable for chloride salt dry and wet environment as claimed in claim 1, characterized in that: The coarse aggregate is granite crushed stone with a particle size of 5-25 mm, and the fine aggregate is river sand with a fineness modulus ≥2.4, a mud content ≤0.5%, and a particle size ≤4.75 mm.
4. The concrete suitable for chloride salt dry and wet environment as claimed in claim 1, characterized in that: The basalt fiber has a length of 6 mm, a diameter of 13-20 μm, and a density of 2.65 g / cm 3 .
5. The concrete suitable for chloride salt dry and wet environment as claimed in claim 1, characterized in that: The pH of the defoamer is 6-8, and the water reducer is a polycarboxylic acid high-performance water reducer with a water reduction efficiency of 35%.
6. The method for preparing concrete suitable for chloride salt dry and wet environments as claimed in any one of claims 1 to 5, characterized in that: include, Wet the inner wall and blades of the mixer, add coarse aggregate and fine aggregate into the mixer, and stir at a speed of 80-120 r / min for 25-35 seconds; After cement, fly ash, silica fume, slag powder and basalt fiber are evenly mixed, add them into a mixer and stir for 25 to 35 seconds, then continue to add water and stir for 25 to 35 seconds; Nano-SiO2, nano-CaCO3, water reducing agent, defoaming agent and remaining water are mixed to prepare a suspension, and then the suspension is vibrated in an ultrasonic oscillator, and then added into a mixer and stirred for 60 seconds to obtain a concrete mixture; The mixture is loaded into the mold, vibrated on a vibration table for 5 to 10 seconds to make it dense, and after plastering, it is left to stand indoors for 24 hours before demoulding. It is then moved into a standard curing room and cured for 28 days to obtain concrete suitable for chloride salt dry and wet environments.
7. The method for preparing concrete according to claim 6, characterized in that: When the remaining water is mixed, the ratio of the weight of water to the total weight of the cement, fly ash, silica fume and slag powder is 0.33-0.38.
Citation Information
Patent Citations
Marine concrete material and preparation method thereof
CN109851294A
Basalt fiber nanocomposite material for concrete and production process of basalt fiber nanocomposite material
CN113105139A
